Co-expression tools for plant biology: opportunities for hypothesis generation and caveats - USADEL, BJÖRN; OBAYASHI, TAKESHI; MUTWIL, MAREK; GIORGI, FEDERICO M; BASSEL, GEORGE W; TANIMOTO, MIMI; CHOW, AMANDA; STEINHAUSER, DIRK; PERSSON, STAFFAN; PROVART, NICHOLAS J (Plant, cell and environment, 2009)
Gene co-expression analysis has emerged in the past 5 years as a powerful tool for gene function prediction. In essence, co-expression analysis asks the question 'what are the genes that are co-expressed, that is, those that show similar expression profiles across many experiments, with my gene of interest?'. Genes that are highly co-expressed may be involved in the biological process or processes of the query gene. This review describes the tools that are available for performing such analyses, how each of these perform, and also discusses statistical issues including how normalization of gene expression data can influence co-expression results, calculation of co-expression scores and P values, and the influence of data sets used for co-expression analysis. Finally, examples from the literature will be presented, wherein co-expression has been used to corroborate and discover various aspects of plant biology.